Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/bfj-01-2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of customers' intention to use online food delivery application through smartphone in Malaysia

Abstract: PurposeThe study aims to examine factors that influence customers' intention to use online food delivery applications using a smartphone. The factors examined in this study are based on the existing theory of Unified Theory of Acceptance and Use of Technology (UTAUT) namely performance expectancy, effort expectancy, social influence, information quality, price-saving orientation and time-saving orientation towards intention to use the applications. Moreover, this research model also has been expanded with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 54 publications
1
42
0
2
Order By: Relevance
“…Despite a number of studies pointing at PE and benefit perceived in VAs toward higher adoption rate (Fan et al, 2022) for providing a pleasurable experience (Tsay and Patterson, 2018), that in turn will add to intention of use and to adoption rates (Almaiah et al, 2019), for the present case scenario didn't show a significant impact toward an increase in user perception or an improved expectation for performance. This bottom line is backed up by the referenced studies (Khalid et al, 2021;Pitchay et al, 2021). From a user skill consideration of VAs usage and adoption, most participants in the 52% spectrum were millennials and digital natives, so, functioning and display of simple commands, searches, and chat natural to the interface did not require any upgrades for the users' technical knowledge (Melián-González et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a number of studies pointing at PE and benefit perceived in VAs toward higher adoption rate (Fan et al, 2022) for providing a pleasurable experience (Tsay and Patterson, 2018), that in turn will add to intention of use and to adoption rates (Almaiah et al, 2019), for the present case scenario didn't show a significant impact toward an increase in user perception or an improved expectation for performance. This bottom line is backed up by the referenced studies (Khalid et al, 2021;Pitchay et al, 2021). From a user skill consideration of VAs usage and adoption, most participants in the 52% spectrum were millennials and digital natives, so, functioning and display of simple commands, searches, and chat natural to the interface did not require any upgrades for the users' technical knowledge (Melián-González et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Pal et al (2021) found that the visual design and information design of the OFD apps are significant factors of customer satisfaction and customer loyalty. Similarly, information quality was a significant factor in consumers' attitudes towards OFD services (Allah Pitchay et al, 2021). Another study by Wen et al (2021) reported that when consumers find it easy to use food delivery apps, they exhibit higher levels of perceived behavioural control, leading to a higher intention to use the food delivery apps.…”
Section: System Operationmentioning
confidence: 99%
“…With the new social norms of social isolation and staying at home, there is a growing demand for OFD services worldwide (Ramos, 2021), especially in Malaysia, the context of the study (Allah Pitchay et al, 2021). It was reported that 38% of new OFD users began using OFD after the Malaysian government imposed movement control, resulting in a 61% increase in OFD customers (Vodus, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, four items of fear of COVID-19, including afraid of coronavirus, uncomfortable thinking of coronavirus, afraid of losing life, and anxiety of watching news of coronavirus suggested by Jian et al (2020), are adopted. Lastly, four items of ITUFPMA, including intention to continue, use in daily life, frequent usage and usage next time, are adapted from Pitchay et al (2021). All items of each construct are measured employing a five-point Likert scale, where "1" denotes "strongly disagree" and "5" denotes "strongly agree."…”
Section: Methodsmentioning
confidence: 99%